The role of news about TFP in U.S. recessions and booms - Renato Faccini; Leonardo Melosi (Federal Reserve Bank of Chicago, 2018)
We develop a general equilibrium model to study the historical contribution of TFP news to the U.S. business cycle. Hiring frictions provide incentives for firms to start hiring ahead of an anticipated improvement in technology. For plausibly calibrated hiring costs, employment gradually rises in response to positive TFP news shocks even under standard preferences. TFP news shocks are identified mainly by current and expected unemployment rates since periods in which average unemployment is relatively high (low) are also periods in which average TFP growth is slow (fast). We work out the noise component of the identified TFP news shocks. Noise captures changes in agents' beliefs about future TFP shocks that do not materialize. These autonomous changes in beliefs have induced fluctuations in the unemployment rate within a two-percentage-point range across the post-war recessions and expansions. After the Great Recession, noise about TFP growth has been the most important factor behind the rise in the employment rate. The index of consumer sentiment and the dismal TFP growth in recent years support these predictions.
Keywords: C11; C51; E32; J64; 330; Unemployment rate; hiring frictions; beliefs; the Great Recession; labor market trends; employment gap; bayesian estimation